Privilege or punish: criminal justice and the challenge of family ties - Markel, Dan (Oxford University Press, 2009)
A survey of family ties benefits -- A normative framework -- Applying the framework to family ties benefits -- A survey of family ties burdens -- Adjusting the normative framework -- Applying the framework to family ties burdens -- Coda